Comprehensive analysis of the codon usage patterns in the envelope glycoprotein E2 gene of the classical swine fever virus. - Ye Chen; Xinxin Li; Xiaojuan Chi; Song Wang; Yanmei Ma; Jilong Chen (PLoS ONE)
The classical swine fever virus (CSFV), circulating worldwide, is a highly contagious virus. Since the emergence of CSFV, it has caused great economic loss in swine industry. The envelope glycoprotein E2 gene of the CSFV is an immunoprotective antigen that induces the immune system to produce neutralizing antibodies. Therefore, it is essential to study the codon usage of the E2 gene of the CSFV. In this study, 140 coding sequences of the E2 gene were analyzed. The value of effective number of codons (ENC) showed low codon usage bias in the E2 gene. Our study showed that codon usage could be described mainly by mutation pressure ENC plot analysis combined with principal component analysis (PCA) and translational selection-correlation analysis between the general average hydropathicity (Gravy) and aromaticity (Aroma), and nucleotides at the third position of codons (A3s, T3s, G3s, C3s and GC3s). Furthermore, the neutrality analysis, which explained the relationship between GC12s and GC3s, revealed that natural selection had a key role compared with mutational bias during the evolution of the E2 gene. These results lay a foundation for further research on the molecular evolution of CSFV.